Interfaith Figures Communication Model in Building Religious Harmony in North Labuhanbatu Regency - Syukur Kholil; Yusnadi Yusnadi; Ibrahim Sihombing (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study about Interfaith Figures Communication Model in Building Religious Harmony in North Labuhanbatu Regency deals with the awareness of interfaith leaders in Labura of the importance of living harmoniously between religious communities, it is important for them to disseminate their understanding of how to build harmony and harmony between religious communities at the root of the clump (community). Therefore, religious figures "berkampenye" to the community about the importance of building a harmonious and harmonious life among communities adhering to different religions in Labura. Research that researchers do is field research (Field Research) which is included in the type of qualitative descriptive research, therefore, in the data collection process, researchers will make field observations behavior in Paud Al Ummah delitua. Thus the creation of dialogue (communication) between religious leaders has rational reasons behind it, including such as the existence of religious plurality in society, the desire to communicate in an effort to understand each other, and the creation of cooperation in society.